Barriers to the Operation of Patient Safety Incident Reporting Systems in Korean General Hospitals - Hwang, Jee-In (Korean Society of Medical Informatics, 2012)
OBJECTIVES: This study aimed to explore the barriers to and factors facilitating the operation of patient safety incident reporting systems. METHODS: A qualitative study that used a methodological triangulation method was conducted. Participants were those who were involved in or responsible for managing incident reporting at hospitals, and they were recruited via a snowballing sampling method. Data were collected via interviews or emails from 42 nurses at 42 general hospitals. A qualitative content analysis was performed to derive the major themes related to barriers to and factors facilitating incident reporting. RESULTS: Participants suggested 96 barriers to incident reporting in their hospitals at the organizational and individual levels. Low reporting rates, especially for near misses, were the most commonly reported issue, followed by poorly designed incident reporting systems and a lack of adequate patient safety leadership by mid-level managers. To resolve and overcome these barriers, 104 recommendations were suggested. The high-priority recommendations included introducing reward systems; improving incident reporting systems, by for instance implementing a variety of reporting channels and ensuring reporter anonymity; and creating a strong safety culture. CONCLUSIONS: The barriers to and factors facilitating incident reporting include various organizational and individual factors. As an important way to address these challenging issues and to improve the incident reporting systems in hospitals, we suggest several feasible methods of doing so.